Effects of acidified seawater on calcification, photosynthetic efficiencies and the recovery processes from strong light exposure in the coral Stylophora pistillata. (20th June 2017) - Nakamura, Takashi; Iguchi, Akira; Suzuki, Atsushi; Sakai, Kazuhiko; Nojiri, Yukihiro
Abstract: The aim of this study was to investigate whether coral photosynthetic efficiencies and recovery processes are affected by CO2 ‐driven ocean acidification in symbiont photosynthesis and coral calcification. We investigated the effects of five CO2 partial pressure ( p CO2 ) levels in adjusted seawater ranging from 300 μatm (pre‐industrial) to 800 μatm (near‐future) and strong and weak light intensity on maximum photosynthetic efficiency and calcification of a branching coral, Stylophora pistillata, as this species has often been used in rearing experiments to investigate the effects of acidified seawater on calcification and photosynthetic algae of corals. We found that, the photosynthetic efficiencies and recovery patterns under different light conditions did not differ among p CO2 treatments. Furthermore, calcification of S. pistillata was not affected by acidified seawater under weak or strong light conditions. Our results indicate that the photosynthetic efficiency and calcification of S. pistillata are insensitive to changes in ocean acidity.